The Implementation of Flash Cards to Teach Vocabulary for Four Grade Students at MI Ma’arif NU Nurul Islam Pronojiwo: English - Selly Itra Purnamasari Selly; Tyas Alhim Mubarok; Ahmad Saifuddin (Journal of English Development, 2024)
Indonesia, English is still taught as a foreign language. This is due to the fact that English is not a common language among Indonesians. Nevertheless, the Indonesian government has included English in the curriculum to be taught in schools, taking into account its significance for international communication. Action research was used to carry out this investigation. One significant advancement in education is the use of action research. It has to do with what the teacher thinks. Do research to obtain a deeper understanding of the teaching and learning process in his own classroom.adding the in-person instructor (Burns, 2010:2). It aims to clarify the cause-and-effect link between the activities and results in order to resolve problems and put into practice workable methods to improve a situation. The researcher used a variety of techniques to collect data on the state of English instruction and education in MI Ma''arif Nurul Islam Pronojiwo's class IV. Initially, the researcher and the English teacher performed interviews and talks. Observations were then conducted to determine the classroom's true state. According to the results of cycles 1 and 2, using flashcards in the teaching and learning process helped students' vocabulary grow. Students' participation in class activities and the learning process is increased when they use flashcards. MI Ma''arif Nu Nurul Islam Pronojiwo students in class IV B served as the study's subjects. The objective of this study is to enhance the language skills of students in the fourth grade.  We started this investigation in July 2023. The tasks were finished in two cycles, and the content was connected to descriptive text.